The Comparison of Propagation Model for Terrestrial Trunked Radio (TETRA) - Kartika R, Ayu; M, Hani’ah; S, Nur Adi (Politeknik Elektronika Negeri Surabaya (PENS), 2013)
A system of digital radio Terrestrial Trunked Radio (TETRA) is designed for communication which need specialility, better privacy, better quality of audio with speed transmission data and access capacity to the internet and telephone network. TETRA system of TMO and DMO operation mode which has wide coverage and reliable than the interference so that the TETRA planning needs a propagation model which corresponding with environment. Therefore, this research compare a pathloss value of calculation of propagation model such as Free Space Loss, Wickson, Bacon, CEPT SE21, Ericsson (9999), ITU-R SM 2028 and Okumura Hata based on the environment are clutter urban, sub urban dan rural. The calculation of pathloss provide that Bacon propagation model is an corresponding model for DMO operation mode with a frequency of 380 MHz, height handhelds 1.5 m and 2 m with pathloss value of 76.82 dB at a distance of 100 m and 113.63 dB at a distance of 1 km while the 400 MHz frequency pathloss value of 77.08 dB at a distance of 100 m and 113.6 dB at a distance of 1 km. The propagation model which corresponding to the TMO operation mode with a frequency of 400 MHz distance of 1 km, the transmitter antenna height (hb) 30 m and receiver antenna height (hm) 1.5 m is a model of Ericsson (9999) on urban clutter with pathloss value of 96.4 dB, the model ITU-R SM2028 in suburban clutter with a pathloss value of 101.13 dB, and the model ITU-R SM2028 on rural clutter with pathloss value of 83.59 dB.Keywords: TETRA, propagation model, urban, suburban, rural